The impact of belonging on enhancing societal values: The novel 'Zahr al-Rumman' by Abdul Hakim Al-Waeli as a model - aluboody, Dhyaa gany aluboody (Sulaimani Journal for Humanities, 2026)
Iraqi society is one of the most diverse societies in religions, sects and languages as well, and no literature can go beyond that, but when you look at literary production in general and novels in particular, you rarely find novelists who depict this, perhaps to preserve the traditional image of society for political, religious and social reasons. However, these factors changed after the change of the regime, and the state of freedom of expression that occurred at the level of culture and awareness made some writers embody those visions, and one of those novels is the novel Blossom of the Pomegranate by Abdul Hakim Al-Waeli, which was published in 2021, and it talks about the theme of belonging in its various dimensions, where it embodies conflict. Between multiple individual and group, historical and cultural affiliations that. It embodies the conflict between multiple individual and group, historical and cultural affiliations that the novel’s characters experience. Hence, the research came to shed light on these ideas, raising a fundamental question that says: What are the conflicts that contemporary people experience regarding the issue of individual and group affiliation? How did the heroes of the novel deal with it?
Keywords: Belonging; personality; place; conflict; pomegranate blossom